2018
DOI: 10.1016/j.powtec.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wall materials on the spray drying efficiency, powder properties and stability of bioactive compounds in tamarillo juice microencapsulation

Abstract: Hydro-and lipo-soluble bioactive compounds, such as anthocyanins and carotenoids, in tamarillo juice were microencapsulated using different wall materials, such as maltodextrin (MD), n-octenyl succinic anhydride modified starch, from waxy maize for high load encapsulation (OSA 1), low viscosity gum Arabic alternative (OSA 2), resistant maltodextrin (RMD) and gum Arabic (GA). The wall materials were characterized according to their physicochemical and functional properties, molecular weight distribution and enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 24 publications
9
64
2
4
Order By: Relevance
“…In contrast, we found that microparticles prepared using 100% maltodextrin as wall material showed the highest encapsulation efficiency (84.20%). A similar result was obtained by Ramakrishnan et al (2018) for microcapsules prepared with tamarillo carotenoids and maltodextrin as encapsulant (84.77%). Kang et al (2019) showed that maltodextrin alone led to a higher encapsulation efficiency of chlorophylls than 5:5 or 3:7 mixtures of gum Arabic and maltodextrin as wall material.…”
Section: Encapsulation Efficiencysupporting
confidence: 84%
“…In contrast, we found that microparticles prepared using 100% maltodextrin as wall material showed the highest encapsulation efficiency (84.20%). A similar result was obtained by Ramakrishnan et al (2018) for microcapsules prepared with tamarillo carotenoids and maltodextrin as encapsulant (84.77%). Kang et al (2019) showed that maltodextrin alone led to a higher encapsulation efficiency of chlorophylls than 5:5 or 3:7 mixtures of gum Arabic and maltodextrin as wall material.…”
Section: Encapsulation Efficiencysupporting
confidence: 84%
“…These compounds were retained more efficiently because the use of a higher-molecular-weight coating material increased the rate of dry-film formation on the surface of the microcapsule [9]. In a microencapsulation study of tamarillo juice, it was observed that coating materials possessing higher molecular weight (maltodextrin, 41.64 g/mol; gum Arabic, 617.32 g/mol) exhibited greater efficacy for both water-and fat-soluble compounds [8].…”
Section: Effect Of Wall Materials Type On Bioactive-compound Rementioning
confidence: 99%
“…Many studies demonstrated the impact of wall material on phytochemical stability. Gum Arabic is very viscous [8]; therefore, it is often used in combination with maltodextrin. Zhang et al [9] revealed a better retention of phenolics in cranberry juice when blended wall material (gum Arabic/maltodextrin) was used, compared to single materials.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization of carotenoids from fruit juices (carrot and tamarillo) was performed by spraydrying in studies comparing the influence of different wall materials (arabic gum and maltodextrin) on chemical and physicochemical properties of the microcapsules [32,33]. The authors observed that arabic gum particles presented greater carotenoid retention and encapsulation efficiency when compared to the maltodextrin ones.…”
Section: Recent Advances In the Stabilization Of Bioactive Compoundsmentioning
confidence: 99%
“…The authors observed that arabic gum particles presented greater carotenoid retention and encapsulation efficiency when compared to the maltodextrin ones. Furthermore, Ramakrishnan et al [32] also analyzed the storage stability of the microcapsules in relation to their antioxidant activity and the amount of carotenoids retained under different storage conditions. It was observed that powders produced with arabic gum stored at 25 • C for 24 days had a higher rate of carotenoid degradation than powders produced with maltodextrin.…”
Section: Recent Advances In the Stabilization Of Bioactive Compoundsmentioning
confidence: 99%